Design and Construction of Asam Gelugur (Garcinia atroviridis Griff.) Slicer - Alvario Kesturi; Saipul Bahri Daulay; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Asam gelugur (Garcinia atrovirdisGriff ), or asam keping  is a type of  nadir tree from Malaysia peninsula. Asam gelugur ( Garcinia atrovirdis Griff) is a dikotiledon type but without kotiledon. Asam gelugur fruit is used by people to make candied fruit, potion, and flavor.The parameters observed were effective capacity, economic value analysis. BEP, NPV and IRR. It was summarized that the effective capacity of the equipment was 708,11 kg/hour, basic costs were Rp. 16,55/kg for the first year,Rp 15,54 for the second year, Rp. 15,19 for the third year, Rp 15,03 for the fourth year, and Rp. 14,93 for the fifth year. Break event point was 20.438,74 kg/year for the first year, 11.018,63 kg/year for the second year, 7882,98 kg/year for the third year, 6317,82 kg/year for the fourth year and 5380,71 kg/year for the fifth year. Net present value was Rp. 1.317.158.537,9. Internal rate of return was 43,56 %, It means that this equipment was worthy to made. Keyword: slicer, Asam gelugur (Garcinia atroviridis Griff.)